2001
DOI: 10.1152/ajpendo.2001.280.3.e534
|View full text |Cite
|
Sign up to set email alerts
|

Impaired PI 3-kinase activation in adipocytes from early growth-restricted male rats

Abstract: Epidemiological studies have established a relationship between early growth restriction and subsequent development of type 2 diabetes. Animal studies have shown that offspring of protein-restricted rats undergo a greater age-related loss of glucose tolerance than controls. The aim of this study was to investigate the possibility that this deterioration of glucose tolerance is associated with changes in adipocyte insulin action. Adipocytes from low-protein offspring had higher basal levels of glucose uptake th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 29 publications
4
77
0
1
Order By: Relevance
“…Increased expression of the insulin receptor [22,23,24] has been observed and this reversed with age [25] possibly providing part of the explanation of the change from increased to decreased insulin sensitivity with age.…”
Section: Studies In Vitromentioning
confidence: 97%
“…Increased expression of the insulin receptor [22,23,24] has been observed and this reversed with age [25] possibly providing part of the explanation of the change from increased to decreased insulin sensitivity with age.…”
Section: Studies In Vitromentioning
confidence: 97%
“…Secondly, they exhibited increased noradrenergic-stimulated lipolysis and a blunted response to insulin-reduced lipolytic action. By contrast, older adult offspring from LP dams underwent an age-related loss of glucose tolerance that paralleled an impaired insulinstimulated PI3K pathway in adipocytes (Ozanne et al 2001). …”
Section: Maternal Reduced Nutritionmentioning
confidence: 99%
“…This molecular characterisation demonstrated that insulin receptor expression is not altered in muscle or adipose tissue from old adult offspring that had been growth-restricted at birth, suggesting that, as in the human situation, the molecular basis of the insulin resistance is a post-receptor defect. Two insulin-signalling molecules were expressed at dramatically reduced levels in the offspring with early growth restriction, namely the atypical protein kinase C (PKC), PKCζ [7] and the p110β subunit of phosphatidylinositol (PI) 3-kinase [8,9]. These proteins are both known to be important in mediating the metabolic actions of insulin [10,11].…”
Section: Introductionmentioning
confidence: 99%